Onion (Allium ascalonicum L.) Plant response Against Multiple Dose of palm oil mill wastewater (LCPKS) and Coconut Water plant growth regulator (PGR) - Bahagia Sibotolungun Sipahutar; Adiwirman Adiwirman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aims to determine onion crop response to multiple doses of palm oil mill wastewater (LCPKS) and coconut water plant growth regulator (PGR). This research has been conducted at the Faculty of Agriculture Experimental Station Riau University Campus Bina Widya km 12.5 Baru Simpang Village Handsome Municipal District of Pekanbaru, for three months, from April to June 2017. This study used a randomized block design (RAK) factorial. The first factor is the palm oil mill effluent consisting of 3 levels, L1 =1 l / m2 , L2 = 2 l/ M2, L3 =3 l/ M2 and the second factor was PGR coconut water which consists of 3 levels, Z1 = 25% = 50% Z2, Z3 = 75%. The parameters were observed consisting of plant height, leaf number, the number of bulbs, tubers convolution, the number of tubers are large, medium and small, fresh tuber weight, and weight in the shelf.The results of the analysis of variance analyzed further using HSD (Honestly Significant Difference) 5%. Administration of LCPKS has significant impact on the number of leaves, number of bulbs, tubers fresh weight, and weight in the shelf. Fresh tuber weight was positively correlated very strongly with weights shelf and moderately correlated wrap the tubers.Keywords: onion, LCPKS, PGR coconut water.